Design and Development of Biosensors for the Detection of Heavy Metal Toxicity - Graziella L. Turdean (International Journal of Electrochemistry)
Many compounds (including heavy metals, HMs) used in different fields of industry and/or agriculture act as inhibitors of enzymes, which, as consequence, are unable to bind the substrate. Even if it is not so sensitive, the method for detecting heavy metal traces using biosensors has a dynamic trend and is largely applied for improving the “life quality”, because of biosensor's sensitivity, selectivity, and simplicity. In the last years, they also become more and more a synergetic combination between biotechnology and microelectronics. Dedicated biosensors were developed for offline and online analysis, and also, their extent and diversity could be called a real “biosensor revolution”. A panel of examples of biosensors: enzyme-, DNA-, imuno-, whole-cell-based biosensors were systematised depending on the reaction type, transduction signal, or analytical performances. The mechanism of enzyme-based biosensor and the kinetic of detection process are described and compared. In this context, is explainable why bioelectronics, nanotechnology, miniaturization, and bioengineering will compete for developing sensitive and selective biosensors able to determine multiple analytes simultaneously and/or integrated in wireless communications systems.